The evolution and current state of bariatric endoscopy in Western countries - Maria Valeria Matteo; Vincenzo Bove; Valerio Pontecorvi; Loredana Gualtieri; Giorgio Carlino; Cristiano Spada; Ivo Boškoski (Clinical Endoscopy)
With the alarmingly increasing prevalence of obesity in the Western world, it has become necessary to provide more acceptable treatment options for patients with obesity. Minimally invasive endoscopic techniques are continuously evolving. Currently, metabolic and bariatric endoscopies encompass several different techniques that can offer significant weight loss and improvement in comorbidities with a favorable safety profile. Restrictive bariatric procedures include the use of intragastric balloons and gastric remodeling techniques with different suturing devices. Several studies have demonstrated the efficacy and safety of these techniques that are widely used in clinical practice. Small intestine-targeted metabolic endoscopy is an intriguing and rapidly evolving field of research, although it is not widespread in routine practice. These techniques include duodenal-jejunal bypass liners, duodenal mucosal resurfacing, and incisionless anastomoses. The aim of this review article is to provide a detailed update on the currently available bariatric endoscopy techniques in Western countries.